Do Patients Access Appropriate Information Online? - Gupta, Amar; Nissan, Michael E.; Bojrab, Dennis I., II; Folbe, Adam; Carron, Michael A. (Facial Plastic Surgery, 2017)
Health care providers should be aware of information available on the Internet to ensure proper patient care. The current analysis assesses the reliability, quality, and readability of internet information describing rhytidectomy. Previously validated survey instruments to assess the reliability, quality, and readability of online websites describing rhytidectomy were used. An internet search using Google with the search term “facelift” was conducted. The first 50 search results were reviewed, and 36 were deemed appropriate to be included in this analysis. Websites were divided based on type of authorship into professional organization, academic, physician based, and unidentified. The validated DISCERN instrument was used to determine reliability, quality, and overall rating of each site. The Flesch Reading Ease Score (FRES) and Flesch–Kincaid Grade Level (FKGL) were used to measure readability. A 1 to 3 point scale was used to rate websites, with a higher number indicating a website that possessed either greater reliability or greater quality. Mean scores for reliability ranged from 1.7 (±0.99) in the academic group to 2.0 (±0.12) in the unidentified group. Mean scores for quality ranged from 1.5 (±0.13) in the unidentified group to 1.7 (±0.38) in the physician-based group. The highest overall rating was 1.4 (±0.22 and ± 0.31, respectively) in the unidentified and physician-based groups. The lowest overall rating was 1 (±0.58) in the academic group. FRESs ranged from 21.6 to 74.6. FKGLs ranged from 6.9 to 13.9. Information available online regarding rhytidectomy may be significantly deficient in reliability, quality, and readability. These deficiencies are present in articles with all types of author affiliations. This underscores the clinicians' duty to provide patients with high-quality information at an adequate level of comprehension.
Keywords: rhytidectomy; DISCERN instrument; readability; online; patient education; Flesch reading ease score